วิกฤตการณ์ผู้ลี้ภัยในยุโรป: ความท้าทายต่อ กฎหมายระหว่างประเทศและบูรณาการของสหภาพยุโรป European Refugee Crisis: Challenges for International Law and European Integration - ลีระศิริ, วรรณภา (CMU Journal of Law and Social Sciences, 2016)
วิกฤตผู้ลี้ภัยในปัจจุบันมีความรุนแรงมากที่สุดนับตั้งแต่สงครามโลกครั้งที่สองเป็นต้นมาโดยมีสาเหตุสำคัญมาจากความรุนแรงและสงครามกลางเมืองในตะวันออกกลางและบางส่วนของแอฟริกาโดยเฉพาะอย่างยิ่งในซีเรีย จำนวนผู้ อพยพไปยุโรปเพื่อขอลี้ภัยเพิ่มขึ้นสูงเป็นประวัติการณ์ในปี พ.ศ. 2558 ส่งผลให้ยุโรปต้องเผชิญกับความท้าทายหลายประการ ได้แก่ การจัดการผู้หนีภัยที่ลักลอบเข้าเมืองอย่างผิดกฎหมายที่มีจำนวนมหาศาล การช่วยเหลือด้านมนุษยธรรมแก่ผู้อพยพ การต่อสู้กับองค์กรอาชญากรรมข้ามชาติที่ลักลอบนำผู้ลี้ภัยเข้ายุโรป และการค้ามนุษย์ ปัญหาด้านความมั่นคงและชายแดนร่วมยุโรป ยุโรปมีหน้าที่ตามพันธกรณีในอนุสัญญาว่าด้วยผู้ลี้ภัย พ.ศ. 2494 ในการให้ความคุ้มครองผู้ลี้ภัย การศึกษานี้พบว่ากลไกด้านการจัดการผู้ลี้ภัยร่วมของยุโรปนั้นไม่มีประสิทธิภาพมากพอที่จะจัดการปัญหาผู้ลี้ภัยในปัจจุบันที่เข้าขั้นวิกฤตได้ ประเทศสมาชิกสหภาพยุโรปต่างออกนโยบายและดำเนินการในเรื่องดังกล่าวโดยยึดเอาผลประโยชน์แห่งชาติของตนเป็นหลัก แสดงให้เห็นถึงความไร้ประสิทธิภาพของสหภาพยุโรปในการบังคับให้รัฐสมาชิกใช้กฎเกณฑ์และแนวปฏิบัติร่วมกัน The current refugee crisis is the most serious one since the end of World War II due to civil wars and violence in the Middle East and parts of Africa, especially in Syria. The number of migrants has skyrocketed since 2015 which causes many challenges for Europe such as managing a large number of asylum seekers who illegally entered Europe; providing humanitarian aids for asylum seekers; fighting human trafficking and smuggling orchestrate by international organized crime syndicates; and European common border and security. Europe has legal duty according to the Refugee Convention 1951 to provide refugees with the protection. This study finds that Common European Asylum System (CEAS) are not effective enough to deal with current migration situation, of which escalates to a crisis level. Members of the EU make decision based on their national interests instead of a common European one, which demonstrates ineffectiveness in enforcing the European laws and protocols among Member States.